2018
DOI: 10.1007/jhep10(2018)116
|View full text |Cite
|
Sign up to set email alerts
|

Localized 4σ and 5σ dijet mass excesses in ALEPH LEP2 four-jet events

Abstract: We investigate an excess observed in hadronic events in the archived LEP2 ALEPH data. This excess was observed at preselection level during data-MC comparisons of four-jet events when no search was being performed. The events are clustered into four jets and paired such that the mass difference between the two dijet systems is minimized. The excess occurs in the region M 1 + M 2 ∼ 110 GeV; about half of the excess is concentrated in the region M 1 ∼ 80 GeV, M 2 ∼ 25 GeV, with a local significance between 4.7σ … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 56 publications
(116 reference statements)
0
9
0
Order By: Relevance
“…We repeat the procedure, increasing or decreasing the smearing by an amount that is independent of p T and η, to obtain other choices of resolution that we need later in our statistical analysis. 10 Our generated statistics are high enough that we may use the smeared MC as our prediction. As a check, we studied smoothing our prediction by fitting it with a single-or double-shouldered Crystal Ball function.…”
Section: B Resonance Line Shapementioning
confidence: 99%
See 1 more Smart Citation
“…We repeat the procedure, increasing or decreasing the smearing by an amount that is independent of p T and η, to obtain other choices of resolution that we need later in our statistical analysis. 10 Our generated statistics are high enough that we may use the smeared MC as our prediction. As a check, we studied smoothing our prediction by fitting it with a single-or double-shouldered Crystal Ball function.…”
Section: B Resonance Line Shapementioning
confidence: 99%
“…[6][7][8] for machine-learning studies on detector-simulated CMS samples, Refs. [9][10][11] for QCD studies on archival ALEPH data, and Ref. [12] for a diphoton analysis with public LHCb data.…”
mentioning
confidence: 99%
“…It was found that different MC event generators have excellent agreement in both the peak as well as in the bulk of the spectra while they can have very large differences in the tails [19]. We stress out that the excellent level of agreement between the different MC event generators is simply due to the fact that they are tuned to the same set of data comprising of LEP measurements at the Z-boson pole [20,21,22,23,24,25,26,27,28,29]. To assess this, we perform a comprehensive analysis of QCD uncertainties on both the fragmentation function parameters and the perturbative shower model using an alternative method and within the same model wherein the default Monash 2013 tune [25] of the Pythia version 8.2.35 event generator [30] is used as our baseline.…”
Section: Introductionmentioning
confidence: 95%
“…Photons from π 0 → γγ dominate bulk (and peak) of spectra most-populated regions of particle spectra may be interpreted as due to the fact that the different MC generators tend to be tuned to roughly the same set of data mostly coming from LEP measurements at the Z-boson pole [25][26][27][28][29][30][31][32][33][34]. Therefore, the envelope spanned by the predictions of the different MC models cannot represent the true estimate of the uncertainty on the predicted spectra.…”
Section: Dominates At High X γmentioning
confidence: 99%